Evaluating the Impact of Public Procurement Reforms on Ghana's Economic Development: Analyze the effectiveness of procurement reforms in Ghana and their contribution to economic growth. - Dzreke, Simon; Dzreke, Semefa (Economics and Business Journal (ECBIS), 2025)
Public procurement plays a pivotal role in driving economic development, particularly in developing nations like Ghana, where government spending accounts for a substantial 70% of the national budget, significantly impacting GDP. This study critically examines the impact of public procurement reforms, notably the Public Procurement Act of 2003 (Act 663) and its subsequent amendments, on Ghana's economic trajectory. These reforms were strategically implemented to enhance transparency, accountability, and efficiency in public resource management. Analysis of key indicators reveals a mixed landscape of outcomes. While the Act has demonstrably improved procurement processes, reduced instances of corruption by a significant 25%, and streamlined public spending efficiency by 15% over the past decade, persistent challenges remain. These include inadequate institutional capacity, inconsistent enforcement of legal frameworks, and limited stakeholder engagement, collectively hindering the full realization of the reforms' transformative potential. Employing a mixed-methods approach, including secondary data analysis and in-depth interviews with government officials, procurement professionals, and civil society representatives, this study provides critical insights. While procurement reforms have made tangible contributions to economic growth  evident in an estimated 10% annual savings in government expenditure significant enhancements are imperative in areas such as capacity building, regulatory enforcement, and fostering robust public-private collaboration. The study concludes with a set of actionable recommendations for stakeholders, including the imperative to strengthen institutional frameworks, promote ethical procurement practices, and cultivate inclusive stakeholder engagement. These measures are crucial for maximizing the impact of procurement reforms and ensuring sustainable economic development in Ghana.